Pengaruh Sikap, Norma Subjektif Dan Persepsi Kontrol Perilaku Terhadap Niat Beli Online Menggunakan Shopee Paylater (Studi Kasus Mahasiswa Di Kota Malang) - Anisia Damayanti; Rois Arifin; Rahmawati Rahmawati (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to find out and analyze the influence of attitudes, subjective norms and perceptions of behavioral control simultaneously and partially on online purchase intentions using Shopee Paylater. This type of research used is quantitative research. The sample in this study were students in the city of Malang who had used Shopee Paylater. Data collection technique used is through the distribution of questionnaires. The analytical method used is multiple linear regression analysis. The results of the study show that attitudes, subjective norms and perceptions of behavioral control simultaneously influence the intention to buy online using Shopee Paylater. Partially, attitudes influence online purchase intentions using Shope Paylater. Meanwhile, subjective norms and perceptions of behavioral control have no effect on online purchase intentions using Shopee Paylater. Keywords: Attitude, Subjective Norm, Perceived Behavior Control, Online Purchase Intention.